Correlates of Public Employees' Motivational Orientations and Motivation Towards in-Service Training in Malaysia - Hashim, Arshad (1993)
Public employees' competence is critical in ensuring the efficiency and effectiveness of the public services. There fore, it is of vital importance for adult educators or HRD managers to understand the major motivational orientations and factors which enhance or inhibit public employees' motivation and effective participation incompetency-based or in-service training programmes. The general objective of this study was to determine public employees' major motivational orientations and motivation toward sin service training and the factors that can be associated with them. Specifically, it aimed to determine: (1) the major motivational orientation sand the level of motivation amongst public employees towards in-service training.